Root canal morphology of mandibular first premolar in a Gujarati population - An in vitro study - Atul Jain; Rachana Bahuguna (Wolters Kluwer Medknow Publications, 2011)
Background: Knowledge about root canal morphology and its frequent variations can exert considerable influence on the success of endodontic treatment. The aim of this study was to survey the root canal morphology of mandibular first premolar teeth in a Gujarati population by decalcification and clearing technique. Methods : One hundred thirty eight extracted mandibular first premolar teeth were collected from a Gujarati population. After decalcifying and clearing, the teeth were examined for tooth length, number of cusps and roots, number and shape of canal orifices and canal types. Results: The average length of mandibular first premolar teeth was 21.2 mm. All the teeth had 2 cusps. One hundred thirty four teeth (97.1%) had one root, and just 4 teeth (2.89%) had two roots. Mesial invagination of root was found in 21 teeth (15.21%). One canal orifice was found in 122 teeth (88.4%) and two canal orifices in 16 teeth (11.59%). Shape of orifices was found to be round in 46 teeth (33.33%), oval in 72 teeth (52.17%) and flattened ribbion in 20 teeth (14.49%). According to Vertucci's classification, Type I canal system was found in 93 teeth (67.39%), Types II,III,IV,V,and VI in 11 teeth (7.97%), 5 teeth (3.62%), 4 teeth (2.89%), 24 teeth (17.39%), and 1 tooth (0.72%) respectively. Conclusion: Mandibular first premolar teeth were mostly found to have one root and Type I canal system.